2009
DOI: 10.1111/j.1399-0012.2008.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum EBV DNA and gammopathy with post‐transplant lymphoproliferative disease

Abstract: Our results confirm an association between EBV in sera and gammopathy with PTLD, and highlight the high specificity of the former analysis. Whether a combination of both analyses will improve the clinical detection of PTLD remains to be evaluated in a larger prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…This pattern was observed in Group 1, where EBV DNA loads appeared to be correlated with disease status. We found similar EBV DNA loads to those previously reported, with most studies showing EBV DNA concentrations ranging from 5.0 × 10 2 to 2.0 × 10 7 copies/ml in whole blood, plasma and serum [37,49,50]. EBV DNA was also detected in CSF at concentrations comparable to plasma, however detectable CSF EBV DNA has been previously reported only in association with acquired immunodeficiency syndrome (AIDS)-related brain lymphoma [51].…”
Section: Discussionsupporting
confidence: 88%
“…This pattern was observed in Group 1, where EBV DNA loads appeared to be correlated with disease status. We found similar EBV DNA loads to those previously reported, with most studies showing EBV DNA concentrations ranging from 5.0 × 10 2 to 2.0 × 10 7 copies/ml in whole blood, plasma and serum [37,49,50]. EBV DNA was also detected in CSF at concentrations comparable to plasma, however detectable CSF EBV DNA has been previously reported only in association with acquired immunodeficiency syndrome (AIDS)-related brain lymphoma [51].…”
Section: Discussionsupporting
confidence: 88%
“…MGUS is considered to be a marker of B cell dysfunction after transplantation. It has been shown that MGUS after HSCT is associated with poor EBV-control and post-transplant lymphoproliferative disease (PTLD) [29, 30], which was also observed in one MGUS patient of our study cohort (patient 7). The other MGUS patient investigated (patient 6) suffered from GvHD, which has been associated with the presence of MGUS likewise [31].…”
Section: Discussionsupporting
confidence: 71%
“…While most lymphomas developed in patients who received GOL 100 mg, as reported 7 , this may be expected given the possibility of dose escalation from 50 mg to 100 mg in patients with persistently active disease and the longer exposure of a greater number of patients to the 100-mg dose. Only 2 patients with lymphoma had evidence of EBV infection, which is noteworthy because the rate of EBV infection is higher among patients with lymphoma associated with immunosuppressive therapy than among patients with other lymphomas 34 . While lymphoma is a known, albeit infrequent, AE that was observed in these studies that were not powered to detect statistical significance of the differential rates of rare AE across dose groups, the potential development of lymphoma with higher doses of GOL requires continued pharmacovigilance.…”
Section: Variablesmentioning
confidence: 98%